Estimating fine-root production in three forestry-drained boreal peatlands dominated by Downy birch (Betula pubescens Ehrh.) - Karim, Md Rezaul; Anttila, Jani; Rinne-Garmston, Katja T.; Sarkkola, Sakari (Taylor & Francis, 2025)
Fine roots of trees significantly contribute to the carbon cycle within boreal forest ecosystems. Despite their importance, fine root production (FRP) remains one of the least understood processes, particularly in deciduous forests. This study estimated fine-root biomass (FRB) and FRP in downy birch (Betula pubescens Ehrh.) dominated stands on drained peatland sites in Central Finland. The stands were classified into three stages: young (10 years), middle-aged (50 years), and mature (80 years). In 2021, the middle-aged stand had the highest total FRB at 751.5 g m−2, followed by the mature stand (329.5 g m−2) and young stand (136.8 g m−2). In 2022, all stands showed increased total FRB, with middle-aged stand reaching 889.5 g m−2. The FRP in the middle-aged stand (445 g m−2 y−1) was more than double that of the mature aged stand (228 g m−2 y−1) and four times larger than in the young stand (107 g m−2 y−1). Soil depth significantly affected FRP, with minimal root activity beyond the second soil layer. Over 90% of total FRP occurred in the top 20 cm soil layer, declining drastically tow.
Keywords: Deciduous tree; ingrowth core; soil depth; soil bulk density; stand age